2011
DOI: 10.1021/bm200417t
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Molecules and Ions Solubilized in Protein Gels: Diffusion in the Thick Fraction of Hen Egg White

Abstract: The thick fraction of hen egg white is a protein hydrogel with an immeasurably high viscosity composed of ∼90% water that can serve as a model system for mammalian mucous membrane. Measurements of the rate constants of diffusion-controlled reactions occurring within the gel (and corresponding activation energies) and electric conductivity revealed that the thick fraction of egg white can be envisioned as a 3D network comprising hydrated protein molecules (held by intermolecular S-S bridges) surrounded by water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…1b), indicating the interaction between protein and water molecules. The thick fraction of EWP could form a 3D network surrounded by water, and with the increase in water, the gel network structure became less compact and texture properties were reduced (Krise & Milosavljevic, 2011). However, the low hardness of the gel network was beneficial for microparticulation, which is important in the preparation of the fat analogue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1b), indicating the interaction between protein and water molecules. The thick fraction of EWP could form a 3D network surrounded by water, and with the increase in water, the gel network structure became less compact and texture properties were reduced (Krise & Milosavljevic, 2011). However, the low hardness of the gel network was beneficial for microparticulation, which is important in the preparation of the fat analogue.…”
Section: Resultsmentioning
confidence: 99%
“…The disulphide bond in EWP is also involved in the whole structure. The viscosity and gel of egg white are derived from the non‐covalent intermolecular interaction between the cysteine residues of mucin monomers and carbohydrate parts (Krise & Milosavljevic, 2011). A three‐dimensional network surrounded by water was formed by hydrated proteins (held by the intermolecular Smurs bridge), which was very similar to the host water (Yu et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Approximately 10 μM of ferric ion were generated per minute of sonication, which corresponds to a concentration of 10 μM hydroxyl radicals (the hydrogen radicals are converted to hydroxyl radicals via reactions with water molecules). The microviscosity of the thick fraction is very similar to that of bulk water, therefore, it is expected that the concentration of radicals generated by acoustic cavitation in water within the thick fraction (where cavitation can occur) at a given sonication time will be comparable to a corresponding amount of bulk water.…”
Section: Resultsmentioning
confidence: 99%
“…Sonochemistry results from ultrasonically induced acoustic cavitation, which is the formation, expansion, and implosive collapse of bubbles within a liquid containing dissolved gas. For cavitation to occur, enough gas must be dissolved, and the liquid medium in which the sonication occurs must be sufficiently large. It was shown before that the solubility of air in the thick fraction of hen albumen is the same as in bulk water , and DSC measurements indicated that some of the water pools may be large enough to allow cavitation . Therefore, despite an immeasurably high macroviscosity, there is a potential for some sonochemical effects to be observed upon exposure of the thick fraction to ultrasound.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation